How body composition influences hearing status by mid-childhood and mid-life: The Longitudinal Study of Australian Children. Issue 10 (October 2018) - Wang, Jing; Sung, Valerie; Lycett, Kate; Carew, Peter; Liu, Richard; Grobler, Anneke; Zubrick, Stephen; Olds, Tim; Wake, Melissa
Abstract Background Hearing loss is a disabling condition whose prevalence rises with age. Obesity—a risk factor common to many non-communicable diseases—now appears to be implicated. We aimed to determine: (1) cross-sectional associations of body composition measures with hearing in mid-childhood and mid-life and (2) its longitudinal associations with 10-year body mass index (BMI) trajectories. Methods Design & Participants: There were 1481 11–12-year-old children and 1266 mothers in the population-based cross-sectional CheckPoint study nested within the Longitudinal Study of Australian Children (LSAC).Anthropometry (CheckPoint): BMI, fat/fat-free mass indices, waist-to-height ratio; LSAC wave 2–6-biennial measured BMI.Audiometry (CheckPoint): Mean hearing threshold across 1, 2 and 4 kHz; hearing loss (threshold > 15 dB HL, better ear).Analysis: Latent class models identifying BMI trajectories; linear/logistic regression quantifying associations of body composition/trajectories with hearing threshold/loss. Results Measures of adiposity, but not fat-free mass, were cross-sectionally associated with hearing. Fat mass index predicted the hearing threshold and loss in children (β 0.6, 95% confidence interval (CI) 0.3–0.8, P < 0.001;, odds ratio (OR) 1.2, 95% CI 1.0–1.4, P = 0.05) and mothers (β 0.8, 95% CI 0.5–1.2, P < 0.001; OR 1.2, 95% CI 1.1–1.4, P = 0.003). Concurrent obesity (OR 1.5, 95% CI 1.1–2.1, P = 0.02) and waist-to-height ratio (WHtR) ≥ 0.6 (OR 1.6, 95% CI 1.2–2.3, P = 0.01) predicted maternal hearing, with similar but attenuated patterns in children. In longitudinal analyses, mothers', but not children's, BMI trajectories predicted hearing (OR for severely obese 3.0, 95% CI 1.4–6.6, P = 0.01). Conclusions Concurrent adiposity and decade-long BMI trajectories showed small, but clear, associations with poor hearing in mid-life women, with emergent patterns by mid-childhood. This suggests that obesity may play a role in the rising global burden of hearing loss. Replication and mechanistic and body compositional studies could elucidate possible causal relationships.